The psychosocial beliefs, experiences and expectations of children living with obesity - Lisa Newson; Nicola Sides; Amineh Rashidi (Health Expectations)
Abstract Background Childhood obesity has been shown to impair psychological health. However, psychological factors are often overlooked in both research evaluations and treatment interventions, and children's perspectives on managing obesity are underexplored. Neglecting psychosocial factors might undermine interventions. This research explored the psychological beliefs, expectations and experiences of children living with obesity (range 7–13) and attending a weight management programme (WMP). Methods Thirty‐four participants (19 females, 15 males, average age 9.5 years) completed a semistructured interview. Recorded interviews were transcribed verbatim and analysed using thematic analysis. Results Four overarching themes were developed: (1) defining health and self‐recognition; (2) external influence; feedback, stigma and comparison; (3) recognising emotions and (4) future expectations: obesity is a reality. These themes interact to influence the children's psychosocial status. Conclusions This study highlights a range of psychosocial and emotional difficulties that children living with obesity experience and suggests that these remain regardless of their attendance at a WMP. Interventions for children living with obesity should address psychosocial factors, including stress management, peer victimisation and handling feedback from others. Patient or Public Contribution As proposed by the two young people acting as patient and public involvement and engagement representatives, the utilisation of scrapbooks as a preinterview tool was particularly helpful in aiding discussion during the interviews. This innovative approach could be considered a valuable methodological technique for investigating sensitive topics with children in future research.